Workload measurement with Bourdon Wiersma and Cardiovascular Load (CVL) methods - Mariawati, Ade Sri; Anggraeni, Shanti Kirana; Nisfulail, Maura Citra; Dewantari, Nustin Merdiana; Herlina, Lely; Umyati, Ani (Universitas Sultan Ageng Tirtayasa, 2024)
A company operating in the sector of workshop production of nuts and bolts requires workers to maintain high levels of speed, precision, and consistency, as well as significant responsibility to deliver the best results for customers. However, while carrying out their tasks, workers may make mistakes due to work fatigue. Therefore, researchers conducted a study to determine the extent of mental and physical workload using the Bourdon Wiersma and Cardiovascular Load (CVL) methods. Bourdon Wiersma is an objective method of measuring workload to determine the level of mental burden in tasks requiring precision, speed, and high consistency, including monotonous tasks. Cardiovascular Load (CVL) involves comparing the increase in heart rate with the maximum heart rate and classifying workload based on the increase in working heart rate compared to the maximum heart rate, expressed as cardiovascular load (% CVL). The research results show that the Bourdon Wiersma percentage for the three job tasks was generally quite good before work and fell within the category of moderate or mild tiredness after work. Additionally, the largest average %CVL occurred in operators at 63%.